The impact of training on hotel service quality Study of a group of classified hotels in Setif - Kraguel, Adel; Kourtel, Farid (Journal of Human Sciences, 2023)
The study aims to know the impact of training on hotel service quality through the dimensions of training (training needs, design of training programs, implementation of training programs, evaluation of training programs), in a group of classified hotels in setif, where the researchers used a descriptive approach adapted to the study, they also adopted a questionnaire as a data collection tool by accepting 65 questionnaires that are the subject of the study. They concluded the existence of a positive impact of training dimensions on hotel service quality at significance level 0،05, they presented some recommendations to strengthen the training culture and value its impact on the service quality provided in the studied hotels.